One jar of magic - Haydu, Corey Ann (Katherine Tegen Books, 2022)
On her twelfth birthday, Rose Alice Anders only catches one small jar of magic in a magic-catching festival on New Year's Eve. In the eyes of her enchantment-gifted father, the most powerful man in town, Rose has failed him and others in the community who hoped she would have his same abilities. Rose hears rumors that some people aren't destined to use magic, and soon she begins to question the expectations that have been placed on her and embarks on a soul-searching pursuit to find out who she is and where she belongs.